2016
DOI: 10.1007/s12035-016-9757-x
|View full text |Cite
|
Sign up to set email alerts
|

The Next Generation of Biomarker Research in Spinal Cord Injury

Abstract: In traumatic spinal cord injury (SCI) patients, the assessment of the exact degree of lesion severity and neurological prognosis has proven to be extremely challenging. The current tools for predicting functional outcome in SCI patients such as clinical examination and magnetic resonance imaging are often inaccessible to unstable or polytraumatized patients, lack sensitivity, and are unreliable in the acute phase of the injury. Multiple candidate protein biomarkers known to be linked to the pathology have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…Mediators of cellular and subcellular oxidative stress have received considerable attention as potential novel neuroprotective targets in acute SCI, including the involved genes, proteins and factors [2,4,8,12]. PAMM is a promising candidate biomarker for SCI because of its dual independent anti-inflammatory and anti-oxidant properties, and because SCI is characterized by both oxidative stress and inflammatory reaction [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mediators of cellular and subcellular oxidative stress have received considerable attention as potential novel neuroprotective targets in acute SCI, including the involved genes, proteins and factors [2,4,8,12]. PAMM is a promising candidate biomarker for SCI because of its dual independent anti-inflammatory and anti-oxidant properties, and because SCI is characterized by both oxidative stress and inflammatory reaction [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…SCI results in varying degrees of functional impairment based on the extent and location of trauma to the cord with high cost to both individual and society. The assessment of both injury severity and long-term neurological prognosis remain challenging after SCI [2]. While injury severity is routinely determined by neurological exam, there are instances where complete neurological testing cannot be performed (coma, intubated or nonverbal patient, presence of cast or other physical barrier).…”
Section: Introductionmentioning
confidence: 99%
“…This display method has been successfully used for the isolation of serine protease inhibitors from a hookworm cDNA library [115], and a series of reports from our research group describe the construction and use of patient-and tissue-specific pVI cDNA libraries expressing colorectal cancer tumor antigens [116] and autoantigens of the autoimmune diseases RA [107], MS [22,117] and clinically isolated syndrome [118]. Recently, our research group has also reported on the construction of a novel human spinal cord cDNA phage display library [119].…”
Section: Cdna Phage Displaymentioning
confidence: 99%
“…Pathophysiologically, the initial mechanical injury damages neurons and initiates a complex secondary injury cascade, leading to progressive cell death, ischemia and inflammation (6). It has been demonstrated that the transcriptome may reflect the pathophysiological state of the cell (7). In a number of recent bioinformatics studies, transcriptome analysis at different time points post-SCI was performed and various molecular events were characterized (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…In a number of recent bioinformatics studies, transcriptome analysis at different time points post-SCI was performed and various molecular events were characterized (8)(9)(10)(11)(12). The immune response, inflammatory-associated functions, vasculature development and neurological functions were demonstrated to serve roles in the development of SCI (6)(7)(8)(9)(10)(11)(12). However, certain molecular alterations that occur in a temporal and spatial manner remain to be elucidated, particularly those that occur during the secondary injury process.…”
Section: Introductionmentioning
confidence: 99%